2013
DOI: 10.1037/a0032753
|View full text |Cite
|
Sign up to set email alerts
|

The development and validation of the Incivility from Customers Scale.

Abstract: Scant research has examined customers as sources of workplace incivility, despite evidence suggesting that mistreatment is more common from organizational outsiders, including customers, than from organizational members (Grandey, Kern, & Frone, 2007; Schat & Kelloway, 2005). As an important step in extending the literature on customer incivility, we conducted two studies to develop and validate a measure of this construct. Study 1 used focus groups of retail and restaurant employees (n = 30) to elicit a list o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
138
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(156 citation statements)
references
References 81 publications
7
138
0
4
Order By: Relevance
“…For example, both Holmvall and Sidhu (2007) and Walsh (2011) demonstrated that customer mistreatment was negatively related to job satisfaction. Similarly, in a sample of employed Canadian university students working in retail services or restaurants, Wilson and Holmvall (2013) also found a negative association between customer mistreatment and job satisfaction. Moreover, Harris (2013) found that customer mistreatment was negatively associated with affective commitment.…”
Section: Individual-level Customer Mistreatment à Outcomesmentioning
confidence: 80%
See 3 more Smart Citations
“…For example, both Holmvall and Sidhu (2007) and Walsh (2011) demonstrated that customer mistreatment was negatively related to job satisfaction. Similarly, in a sample of employed Canadian university students working in retail services or restaurants, Wilson and Holmvall (2013) also found a negative association between customer mistreatment and job satisfaction. Moreover, Harris (2013) found that customer mistreatment was negatively associated with affective commitment.…”
Section: Individual-level Customer Mistreatment à Outcomesmentioning
confidence: 80%
“…Using a sample of nurses and a sample of public service workers, Merecz, Drabek, and Mo´scicka (2009) reported positive relationships between customer mistreatment and mental health problems, psychosomatic health complaints, and anxiety and insomnia. As another example, Wilson and Holmvall (2013) found that customer mistreatment was positively associated with jobrelated psychological strain. Yet, Sliter et al (2011) did not find a significant relationship between customer mistreatment and physical health complaints reported three months later.…”
Section: Individual-level Customer Mistreatment à Outcomesmentioning
confidence: 96%
See 2 more Smart Citations
“…There are several scales to assess various aspects of incivility such as incivility from supervisors and coworkers (Cortina et al, 2001;Martin & Hine, 2005), incivility from customers (Wilson & Holmvall, 2013), and enacted incivility (Blau & Andersson, 2005). There are also studies that illustrate the incidence and nature of workplace incivility (e.g., Cortina et al, 2001;Lim & Cortina, 2005;MinerRubino & Cortina, 2004) and the outcomes of experienced incivility (e.g., Caza & Cortina, 2007;Giumetti et al, 2013;Lim & Teo, 2009;Lim et al, 2008).…”
Section: Introductionmentioning
confidence: 97%